Léon l’Africain à la « rencontre » de la Renaissance - Abdelkrim Benslim (Multilinguales)
The purpose of this article is to study the travel narrative of Hassan el-Wazzan, alias Jean-Léon l’Africain; he proposes to show how this half -real and half-fictional character can be considered as a "man of the Renaissance" and how, in his captivity in Rome, he was able to transform his prison stay into a moment of learning new knowledge, reflection and scriptural creativity. A veritable initiatory quest, this forced exile enabled him, thanks to his sagacity and his wisdom, to enter fully into the Italian Renaissance on the same level. We shall have to apprehend the experience of Leon’s departure from his own as a true story to be read in both Europe and the Maghreb.